INDEKS GLIKEMIK DAN BEBAN GLIKEMIK COOKIES DENGAN SUBSTITUSI TEPUNG BONGGOL PISANG - Farah Mumpuni (2023)
The increasing prevalence of Diabetes Mellitus (DM) over the years makes this disease noteworthy. Consumption of foods low on the glycemic index and high in fiber can be an effort to reduce the risk of developing DMT2. Consumption of high-fiber foods can delay the increase in blood glucose levels in the body. One of the local foodstuffs that contain high fiber is banana corm. The purpose of this study was to determine the GI and GL values of cookies with banana corm flour substitution. This study used a true experimental study design with 10 healthy adult subjects. This study was divided into two groups, namely the control group which was given a reference food in the form of 50 grams of pure glucose and the treatment group which was given the test food in the form of cookies substituted with banana corm flour with a ratio of banana corm flour and wheat flour 25%: 75% (F1) , 50%:50% (F2), 75%:25% (F3), 100%:0% (F4). The results of the intervention showed that the mean blood glucose response in the treatment group was lower when compared to the control group. GI value of cookies with banana corm flour substitution F1 = 26.13 ; F2 = 16.66 ; F3 = 12.83 ; F4 = 8.62 and GL value of cookies with banana corm flour substitution F1 = 5.76 ; F2 = 3.64 ; F3 = 2.81 ; F4 = 1.89. The GI and LG values of cookies with banana corm flour substitution were low. The results of the oneway anova test showed p <0.05 on GI and LG, so it can be concluded that there is an effect of banana corm flour substitution on GI and LG values. The more the proportion of banana corm flour, the lower the GI and LG values of the cookies.